1999
DOI: 10.1074/jbc.274.45.32402
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Biophysical Characterization of a New [2Fe-2S] Ferredoxin from Azotobacter vinelandii, a Putative [Fe-S] Cluster Assembly/Repair Protein

Abstract: During the purification of site-directed mutant variants of2؉/؉ cluster by UV/visible, CD, and EPR spectroscopies with a reduction potential of ؊344 mV versus the standard hydrogen electrode. When overexpressed in Escherichia coli, recombinant FdIV holoprotein was successfully assembled. However, the polypeptide of the recombinant protein was modified in some way such that the apoprotein molecular mass increased by 52 Da. Antibodies raised against FdIV and EPR spectroscopy were used to examine the relative lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 80 publications
2
38
0
Order By: Relevance
“…2B), contained negatively signed peaks at 348, 390, 530, and 620 nm, a dominant positive peak at 460 nm, and low intensity positive peaks at 315, 370, 600, and 700 nm. These features resemble those of [2Fe-2S] type clusters (36,37), in which only minor differences in peak maxima, probably reflecting differences in the local protein environment, are usually found.…”
Section: Resultsmentioning
confidence: 59%
“…2B), contained negatively signed peaks at 348, 390, 530, and 620 nm, a dominant positive peak at 460 nm, and low intensity positive peaks at 315, 370, 600, and 700 nm. These features resemble those of [2Fe-2S] type clusters (36,37), in which only minor differences in peak maxima, probably reflecting differences in the local protein environment, are usually found.…”
Section: Resultsmentioning
confidence: 59%
“…The function of ferredoxin encoded by the gene fdx is not known, although the gene fdx has an essential role in overall assembly of iron-sulfur clusters (28). It has also been postulated that ferredoxin is important for biogenesis or repair of iron-sulfur clusters in Azotobacter vinelandii (33) and in Saccharomyces cerevisiae (34). Nevertheless, none of these proteins seem to have the activity that can directly remove the damaged iron-sulfur clusters from proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli ferredoxin [2Fe-2S] cluster has been used as an example in this study, because the gene encoding ferredoxin is highly conserved in both eukaryotic and prokaryotic organisms (27,28,33,34). To increase the amount of ferredoxin in E. coli cells, the protein was partially overproduced using the expression plasmid pTFDX, in which a His tag was fused to the C terminus of the ferredoxin polypeptide.…”
Section: Ferredoxin [2fe-2s] Clusters Are Transiently Modified When Ementioning
confidence: 99%
“…As a matter of fact, several recent studies have shown that Fdx is absolutely required for proper cellular function. In A. vinelandii, disruption of the corresponding gene is lethal (31). In yeast, the corresponding protein, named Yah1p, is also essential, and depletion of Yah1p resulted in accumulation of iron within mitochondria and defects in the incorporation of Fe-S clusters in both mitochondrial and cytosolic Fe-S enzymes (15).…”
Section: Discussionmentioning
confidence: 99%